2006
DOI: 10.1128/jcm.01482-06
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Helicobacter pylori Infection in Rhesus Macaques Is Most Consistent with Oral-Oral Transmission

Abstract: Socially housed rhesus monkeys rapidly acquired Helicobacter pylori infection, although the organism was rarely cultivated from saliva, feces, or the environment. Since the concentrations of H. pylori in vomit were compatible with what is known about the infectious dose, our results are most consistent with an oral-oral means of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The apparent competition between H. pylori and H. suis in the antrum is striking, particularly since each species tends to occupy a distinct compartment of the stomach. Experimentally-inoculated H. pylori is found predominately in the antrum [47], while non- pylori-Helicobacter spp. are routinely observed within or adjacent to the parietal cells of the corpus [48], with a reported tropism for the fundus of the stomach [19].…”
Section: Resultsmentioning
confidence: 99%
“…The apparent competition between H. pylori and H. suis in the antrum is striking, particularly since each species tends to occupy a distinct compartment of the stomach. Experimentally-inoculated H. pylori is found predominately in the antrum [47], while non- pylori-Helicobacter spp. are routinely observed within or adjacent to the parietal cells of the corpus [48], with a reported tropism for the fundus of the stomach [19].…”
Section: Resultsmentioning
confidence: 99%
“…Socially housed rhesus monkeys rapidly acquire H. pylori infection. Newborns from infected dams are more commonly infected than those from uninfected dams, particularly during the peripartum period, suggesting that close contact during this time facilitates oral-oral transmission (213,214). Once acquired, infection is associated with chronic gastritis that resembles that seen in humans.…”
Section: Gastric Helicobacters Associated With Nonhuman Primatesmentioning
confidence: 99%
“…In human patients presenting severe pathology and clinical symptoms associated with the presence of non-H. pylori helicobacters, treatment is indicated, although the efficacy of such 214 HAESEBROUCK ET AL. CLIN.…”
Section: Gastric Disease In Humans Infected With Non-h Pylori Helicomentioning
confidence: 99%
“…Fecal-oral transmission may be possible under conditions in which H pylori survive transit through the lower gastrointestinal tract, which is uncommon in healthy people. [17][18][19][20] An experimental study in humans confirmed that H pylori is not typically culturable in normal human feces, but, when diarrhea is induced in naturally infected volunteers, up to 20% of stool samples contain culturable H pylori. 19 The same study showed that when emesis is induced in infected volunteers, all samples of vomitus contain culturable H pylori, often in high numbers.…”
Section: Bacterial Factors Transmission and Entrymentioning
confidence: 99%